Unha cantiga lésbica amatoria no trobadorismo galego-portugués. - CALLÓN, CARLOS (Scripta, 2020)
The cantiga «Dizia la ben-talhada», attributed to the Galician-Portuguese troubadour Pedr'Eanes Solaz, appeared in most of the editions of the 19th and 20th century (and in some of the 21st) modificating feminine pronouns into masculine, to denote a heterosexual relationship that does not appear in the text. In this article are developed the different interpretive hypotheses on composition, in dialogue with other similar medieval literary texts (Romance, mid-Latin and Andalusian). It is concluded then that the most likely hypothesis, in the light of the available data, is that it is an amateur composition between two women and that as such, it should be restored to its edition..